2020
DOI: 10.1001/jamainternmed.2020.3288
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Emergency Department Visits and Hospital Admissions in Health Care Systems in 5 States in the First Months of the COVID-19 Pandemic in the US

Abstract: IMPORTANCE As coronavirus disease 2019 (COVID-19) spread throughout the US in the early months of 2020, acute care delivery changed to accommodate an influx of patients with a highly contagious infection about which little was known. OBJECTIVE To examine trends in emergency department (ED) visits and visits that led to hospitalizations covering a 4-month period leading up to and during the COVID-19 outbreak in the US. DESIGN, SETTING, AND PARTICIPANTS This retrospective, observational, cross-sectional study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
452
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(506 citation statements)
references
References 8 publications
47
452
2
5
Order By: Relevance
“…Third, diagnostic rates overall in the network are about 30% lower for both psychiatric and physical disorders since the onset of COVID-19 (see appendix p 45 ), consistent with other evidence for reduced presentations in the USA. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Third, diagnostic rates overall in the network are about 30% lower for both psychiatric and physical disorders since the onset of COVID-19 (see appendix p 45 ), consistent with other evidence for reduced presentations in the USA. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the current study showed a two-fold increase in red zone admissions despite the significant decrease in ED visits. Jeffrey et al supported this finding in their study, which showed an increased rate of hospital admissions from the ED, despite a decrease in ED visits by more than 40% [ 11 ].…”
Section: Discussionmentioning
confidence: 80%
“…1,2 However, patients' reluctance to seek healthcare during the pandemic, particularly for minor ailments, may lead to unexpected outpatient antimicrobial stewardship gains. Jeffery et al 3 reported an inverse relationship between COVID-19 cases and daily counts of emergency department visits in 5 US states between January and April of 2020. Diagnoses were not reported in this study, and the authors concluded that clinicians should reinforce to patients the importance of seeking emergency department care for serious conditions.…”
mentioning
confidence: 99%